Resolvin D1 attenuates CCl4 Induced Liver Fibrosis by Inhibiting Autophagy-Mediated HSC activation via AKT/mTOR Pathway - Li, Jiahuan; Deng, Xiaoling; Wang, Shuhan; Jiang, Qianqian; Xu, Keshu (Frontiers in Pharmacology, 2021)
Resolvin D1(RvD1) was previously reported to relieve inflammation and liver damage in several liver diseases, but its potential role in liver fibrosis remains elusive. The aim of our study was to investigate the effects and underlying mechanisms of RvD1 in hepatic autophagy in liver fibrosis. In vivo, male C57BL/6 mice were intraperitoneally injected with 20% CCl4 (5 ml/kg) twice weekly for 6 weeks to establish liver fibrosis model. RvD1 (100 ng or 300 ng/mouse) was added daily in the last 2 weeks of the modeling period. In vitro, lipopolysaccharide (LPS)-activated LX-2 cells were co-treated with increasing concentrations (2.5-10 nM) of RvD1. The degree of liver injury was measured by detecting serum AST and ALT contents and H&E staining. Hepatic fibrosis was assessed by masson's trichrome staining and metavir scoring. The qRT-PCR, western blot, immunohistochemistry, and immunofluorescence were applied to liver tissue or LPS-activated LX-2 cells to explore the protective effects of RvD1 in liver fibrosis. Our findings reported that RvD1 significantly attenuated CCl4 induced liver injury and fibrosis by decreasing plasma AST and ALT levels, reducing collagen I and α-SMA accumulation and other pro-fibrotic genes (CTGF, TIMP-1 and Vimentin) expressions in mouse liver, restoring damaged histological architecture and improving hepatic fibrosis scores. In vitro, RvD1 also repressed the LPS induced LX-2 cells activation and proliferation. These significant improvements mainly attributed to RvD1 markedly inhibiting autophagy in the process of HSC activation, as demonstrated by decreased ratio of LC3-II/I and elevated p62 after RvD1 treatment. In addition, using AZD5363 (an AKT inhibitor that activates autophagy) and AZD8055 (an mTOR inhibitor, another autophagy activator), we further verified that RvD1 suppressed autophagy-mediated HSC activation and alleviated liver fibrosis partly through AKT/mTOR pathway. Overall, these results demonstrate that RvD1 treatment is expected to become a novel therapeutic strategy against liver fibrosis.